The pains of detainment: Experience of time and coping strategies at immigration detention centres - Gashi, Liridona (Theoretical criminology, 2021)
In most jurisdictions, immigration detention centres are seen as an important part of the immigration control system. Research suggests that stressful waiting and the experience of uncertainty are common at such institutions. However, few empirical studies show how detainees manage these matters. In this article, we draw on fieldwork conducted at the only detention centre in Norway. Detainees described their situation as frustrating and emotionally challenging; and we show how they as a response developed a set of coping techniques aimed at ‘making their own time’. The most important were: (1) living in ‘slow motion’; (2) censorious attacks directed at the institution to break the monotony; (3) the use of benzodiazepines to regulate the perception of time; and (4) religious practices to connect the present with the future. We conclude that when investigating coping- and resistance strategies, we should not overlook the temporal aspects of them and their implications.